Base-triggered self-amplifying degradable polyurethanes with the ability to translate local stimulation to continuous long-range degradation. Issue 12 (9th March 2020) - Xu, Yanhua; Sen, Samya; Wu, Qiong; Zhong, Xujia; Ewoldt, Randy H.; Zimmerman, Steven C.
Abstract : A new type of base-triggered self-amplifying degradable polyurethane is reported that degrades under mild conditions, with the release of increasing amounts of amine product leading to self-amplified degradation. Abstract : A new type of base-triggered self-amplifying degradable polyurethane is reported that degrades under mild conditions, with the release of increasing amounts of amine product leading to self-amplified degradation. The polymer incorporates a base-sensitive Fmoc-derivative into every repeating unit to enable highly sensitive amine amplified degradation. A sigmoidal degradation curve for the linear polymer was observed consistent with a self-amplifying degradation mechanism. An analogous cross-linked polyurethane gel was prepared and also found to undergo amplified breakdown. In this case, a trace amount of localized base initiates the degradation, which in turn propagates through the material in an amplified manner. The results demonstrate the potential utility of these new generation polyurethanes in enhanced disposability and as stimuli responsive materials.